2022
DOI: 10.3390/su141912925
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Development and Strategic Approaches for Contemporary Higher Education

Abstract: Due to the increasing appearance of global contagious diseases such as COVID-19, the goal of this research is to directly and explicitly advance the learning motivation, interests, and performance of online course participants into developing sustainable development and strategic approaches to discover the effective solution of the research question: how to provide the most effective online courses of sustainable development strategy for contemporary higher education in order to advance the student’s learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Subsequently, ref. [ 47 ] addressed that the presented expert’s and professional’s collected questionnaires should be at least over ten percent of surveyed data to ensure the least errors of research validity and reliability due to the date-collection Delphi method. Thus, considering over ten percent of the 250-person surveyed data, there were 20 experts, professionals, and specialists who were in-person interviewed for expertly weighted questionnaires in the ANP of qualitative analysis [ 48 ].…”
Section: Results Designmentioning
confidence: 99%
“…Subsequently, ref. [ 47 ] addressed that the presented expert’s and professional’s collected questionnaires should be at least over ten percent of surveyed data to ensure the least errors of research validity and reliability due to the date-collection Delphi method. Thus, considering over ten percent of the 250-person surveyed data, there were 20 experts, professionals, and specialists who were in-person interviewed for expertly weighted questionnaires in the ANP of qualitative analysis [ 48 ].…”
Section: Results Designmentioning
confidence: 99%
“…Even the amount of semen is regarded as a test of attractiveness, which inadvertently affects males to ejaculate as long as they have sex. Under this pressure, it is difficult to enjoy sex and to remain erect [11][12][13][14][15]. This situation wrecks the sexual interest and relationship of a couple as shown in Figure 2.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The United Nations have suggested these goals as the path to follow in order to achieve sustainable development. Some studies have shown the importance of aligning human activities to SDGs (Deveci et al, 2022; Hsieh, 2022; Jagaba et al, 2022). Nevertheless, there is not a clear approach to the contribution of research to the SDGs, especially for countries like Peru.…”
Section: Introductionmentioning
confidence: 99%